Bloodlines - Mead, Richelle (Mead, Richelle. Bloodlines novel., 2011)
When alchemist Sydney is ordered into hiding to protect the life of Moroi princess Jill Dragomir, the last place she expects to be sent is a human private school in Palm Springs, California. But at their new school, the drama is only just beginning.